My Past is Now: Further Memoirs of a Labour Lawyer - Newell, Dianne (Labour / Le Travail, 1995)
The article reviews the book, "My Past Is Now: Further Memoirs of a Labour Lawyer," by John Stanton.
Keywords: BOOKS -- Reviews; MEMOIRS; MY Past Is Now: Further Memoirs for a Labour Lawyer (Book); Nonfiction; STANTON, John